1997
DOI: 10.1515/cclm.1997.35.7.523
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Lactate Dehydrogenase Isoenzyme Pattern in Pleural Effusions

Abstract: Summary: Lactate dehydrogenase isoenzymes have been used to classify the nature of pleural effusion. Nevertheless, studies have reported conflicting results. The objective of this study was to evaluate the diagnostic value of lactate dehydrogenase isoenzymes in the analysis of pleural effusions.Pleural fluid samples obtained from three respective diagnostic groups: group I transudate (n = 23), group II parapneumonic effusion (n = 29) and group III malignant effusion or pleuritis carcinomatosa (n = 41) were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Hypoxic areas in malignancy have been shown to increase (Fantin et al 2006). Human LDH-4 activity in PE and AF were found to be signi cantly higher in malignancy than in nonmalignancy (Cobben et al 1997;Sevinc et al 2005). These studies included patients with non-blood cancers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hypoxic areas in malignancy have been shown to increase (Fantin et al 2006). Human LDH-4 activity in PE and AF were found to be signi cantly higher in malignancy than in nonmalignancy (Cobben et al 1997;Sevinc et al 2005). These studies included patients with non-blood cancers.…”
Section: Discussionmentioning
confidence: 98%
“…This study demonstrated that LDH-1 activity in PE or AF increased in cats with CHF and liver disease. In humans, CHF increases the percentile of LDH-1 activity in PE and AF due to aerobic conditions in heart tissue (Firth et al 1995;Cobben et al 1997;Sevinc et al 2005). Increasing in LDH-1 activity in AF was also observed in patients with chronic liver disease (Sevinc et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation